Some Opial-Type Inequalities on Time Scales. (24th May 2011) - Saker, S. H.
Abstract : We will prove some dynamic inequalities of Opial type on time scales which not only extend some results in the literature but also improve some of them. Some discrete inequalities are derived from the main results as special cases.